T-Follicular Regulatory Cells: Potential Therapeutic Targets in Rheumatoid Arthritis - Ding, Tingting; Niu, Hongqing; Zhao, Xiangcong; Gao, Chong; Li, Xiaofeng; Wang, Caihong (Frontiers in Immunology, 2019)
Rheumatoid arthritis (RA) is an incurable aggressive chronic inflammatory joint disease with a worldwide prevalence. High levels of autoantibodies and chronic inflammation may be involved in the pathology. Notably, T follicular regulatory (Tfr) cells are critical mediators of T follicular helper (Tfh) cell generation and antibody production in the germinal center (GC) reaction. Changes in the number and function of Tfr cells may lead to dysregulation of the GC reaction and the production of aberrant autoantibodies. Regulation of the function and number of Tfr cells could be an effective strategy for precisely controlling antibody production, reestablishing immune homeostasis, and thereby improving the outcome of RA. This review summarizes advances in our understanding of the biology and functions of Tfr cells. The involvement of Tfr cells and other immune cell subsets in RA is also discussed. Furthermore, we highlight the potential therapeutic targets related to Tfr cells and restoring the Tfr/Tfh balance via cytokines, microRNAs, the mammalian target of rapamycin (mTOR) signaling pathway, and the gut microbiota, which will facilitate further research on RA and other immune-mediated diseases.